Care Burden and Social Support Levels of Caregivers of Patients with Chronic Obstructive Pulmonary Disease. Issue 4 (July 2016) - Göriş, Songül; Kılıç, Züleyha; Elmalı, Ferhan; Tutar, Nuri; Takcı, Özlem
Abstract : This descriptive study was conducted to determine the care burden and social support levels of caregivers to patients with chronic obstructive pulmonary disease (COPD). The primary caregivers of 112 patients with COPD hospitalized in the chest diseases service of a university hospital were involved in the study. Data of the study were collected by using the Patient and Caregiver Information Form, which was prepared by reviewing the literature, Katz Index of Independence in Activities of Daily Living, Zarit Burden Interview, and Multidimensional Scale of Perceived Social Support. While the care burden mean score of caregivers of patients with COPD was 40.91 ± 20.58, the mean score of Multidimensional Scale of Perceived Social Support was 54.13 ± 18.84. In this study, it was determined that female caregivers, as well as individuals stating that their physical and psychological health was affected and those having difficulty giving care and needing help, had higher levels of care burden, whereas the spouses, as well as individuals with lower levels of income and those stating that their physical and psychological health was affected, had lower levels of social support.